Naked Waneek Horn-Miller: Incredible performances call for reinterpretation - Henrie, Karine Jacynthe (University of Ottawa (Canada), 2003)
At the eve of the Summer Olympics in 2000, images of women athletes in the media were numerous. Where people might have expected action shots of these athletes, the burst of coverage was dedicated to women athletes who had decided to pose naked. In Canada, Waneek Horn-Miller, assistant captain of the Canadian women's water polo team, posed naked for the cover of Time magazine. Was the cover promoting Horn-Miller's sexuality, sensuality and femininity more than her athletic skills and abilities? How was the media constructing Horn-Miller's experience of posing naked? How was she, herself; constructing her experience? What identities was she performing on the cover? A semiotic analysis of the Time cover as well as a qualitative analysis of 10 newspaper articles and an interview conducted with Horn-Miller suggested that, rather than supporting and promoting dominant discourses of femininity, gender and race, the picture offered a challenge to those discourses and forced the viewers to think of the naked body of Horn-Miller in terms of new language and new vocabulary. Furthermore, my poststructural interpretation revealed that, while the media have strategically constructed their texts to assign Horn-Miller with a singular, fixed and unified "feminine-looking-woman-athlete" subjectivity mainly influenced by the dominant femininity discourse, Horn-Miller's speech highlighted how she performed fluid, fragmented and contradictory identities that were influenced by the adoption of various subject positions in different discourses, notably the femininity, sport and Native discourses.
Keywords: Women's Studies.; Mass Communications.; Recreation.